Subject-specific musculoskeletal modelling in patients before and after total hip arthroplasty*. Issue 15 (17th November 2016) - Wesseling, Mariska; De Groote, Friedl; Meyer, Christophe; Corten, Kristoff; Simon, Jean-Pierre; Desloovere, Kaat; Jonkers, Ilse
Abstract: The goal of this study was to define the effect on hip contact forces of including subject-specific moment generating capacity in the musculoskeletal model by scaling isometric muscle strength and by including geometrical information in control subjects, hip osteoarthritis and total hip arthroplasty patients. Scaling based on dynamometer measurements decreased the strength of all flexor and abductor muscles. This resulted in a model that lacked the capacity to generate joint moments required during functional activities. Scaling muscle forces based on functional activities and inclusion of MRI-based geometrical detail did not compromise the model strength and resulted in hip contact forces comparable to previously reported measured contact forces.